Socialization and Education on the Prevention of Bullying and Sexual Violence at the Al-Barkah Islamic Study Group - Nada Shofi Nurfazri; Putri Novi Rahmayani; Nasyia Alifa Fadya; Achmad Harristhana Mauldfi Sastraatmadja; Oyoh Bariah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research discusses socialization and education on the prevention of bullying and sexual violence at Majlis Taklim Al-Barkah. The main focus is to provide an understanding of the meaning, impact, and ways to prevent such behavior based on Islamic law, including the postulates of the Qur'an and Hadith. Education also includes Islamic legal sanctions against perpetrators, as well as efforts to build public awareness of the importance of a safe and inclusive environment. This community service activity succeeded in increasing participants' awareness of the issue through a participatory approach that included the delivery of materials, discussions, and questions and answers. The results of the activity showed that participants could understand the material well and actively participate, which is expected to produce positive changes in daily life.